Does a case-based online group project increase students' satisfaction with interaction in online courses?. (November 2016) - Lee, Sang Joon; Ngampornchai, Anchalee; Trail-Constant, Trudian; Abril, Andres; Srinivasan, Sandhya
Due to the realistic, complex natures of authentic cases involved in case-based learning, the use of group work has been encouraged and expected to enhance the quality of interaction among participants and to improve students' learning experiences. The purpose of this study was to investigate whether the case-based online group work increased students' satisfaction with interaction among students in an online course. Findings of this study revealed that the group assignment did not have an effect on students' satisfaction with online interactions. Instead, students' perceptions of the importance of group work were associated with their satisfaction with interaction in the online course.